Key Drivers of Police Performance (Personnel Teaching Staff Coordinator): Leadership, Work Discipline, Personal Competence, and Interpersonal Communication - Tianovita Juliani Hutahaean; Erfa Okta Lussianda; Ummu Ajirah Abdul Rauf (International Journal of Information System and Innovation Management (IJISIM), 2023)
This study aims to determine the effect of leadership, work discipline, personality competence and interpersonal communication on the performance of members of the Polri teaching staff coordinator (Coorgadik) of Riau State Police School. The population of this study was 50 members of the Polri teaching staff coordinator (Coorgadik) of Riau State Police School. The total population of the Polri teaching staff coordinator (Coorgadik) of Riau State Police School is 50 people, the sample is taken by census technique. The results of this study prove the results of the regression in the regression equation that leadership, work discipline, interpersonal communication have a positive effect and personality competence has a negative effect. The result of the t test shows that partially the independent variable has a significant effect on the dependent variable. The result of the F test shows that the independent variable simultaneously has a significant effect on the dependent variable.